Crustal thermal structure of the Farafra oasis, Egypt, based on airborne potential field data. (September 2018) - Abdel Zaher, M.; Elbarbary, S.; Sultan, S.A.; El-Qady, G.; Ismail, A.; Takla, E.M.
Highlights: Integrated regional geophysical studies were done in the Farafra area. The objective is to evaluate the geothermal potential in the Farafra oasis. Six zones of high geothermal probability are recognized in the Farafra oasis. Direct use is the optimum utilization of geothermal resources in Farafra oasis. Abstract: The Farafra oasis is one of the most interesting and promising areas for geothermal energy development in Egypt. The objective of the present study is to evaluate the geothermal potential in the Farafra oasis and its suitability for geothermal development in the Western Desert using different tools such as remote sensing, seismic events, and aeromagnetic and aerogravity data. Remote sensing (Landsat 8 ETM+) was utilized to estimate the land surface temperature (LST) in the Farafra oasis. The resultant map of LSTs indicates that the surface temperature of the Farafra area ranges from 10 °C to 30 °C and that the mean surface temperature of the whole area is approximately 26 °C. Most earthquake events are located to the east and northeast of the Farafra oasis (toward the Bahariya Oasis). However, the highest magnitude event (4.62) is located near the eastern border of the Farafra oasis. One event with a magnitude of 3.08 is located to the south and within the Farafra outline. The distributions of low-magnitude earthquake events can provide information about the locations of active faults, which indicate possible fracture permeability. The interpretation of aeromagnetic data indicates that the Curie point depth (CPD) ranges from 16 km to 26 km with an average of 22 km. The CPDs increase toward the center and north of the Farafra oasis and decrease westward. The interpretation of aerogravity data shows maximum anomalies above four main localities: Ain-Dalla, Bir-Sitta, northeast of Bir-Sitta and at the southern margin of the Farafra oasis, which indicates the existence of vertical or near-vertical contacts (faults) in these areas and provides a good correlation with structural lines on the geological map. Linear features striking NE-SW are pronounced on the tilt gradient map.